Dampak Kebijakan Perberasan pada Pasar Beras dan Kesejahteraan Produsen dan Konsumen Beras di Indonesia - Edy Siswanto; Bonar Marulitua Sinaga; . Harianto (Jurnal Ilmu Pertanian Indonesia, 2018)
Rice demand in Indonesia increases every year so it makes the big gap between production and consumption of rice. Excess demand is covered by rice import which causes domestic rice price responds the global rice price movements that harm both producers and consumers. So, the policy instruments that could reduce dependence on rice import and can provide benefits to producers and consumers of rice is very needed. The objectives of this study were to analyze the impact of rice policy on rice market and the welfare of rice producers and consumers. This study uses annual time series data and simultaneous equations model with two stages least squares method. The analysis showed that rice policy changes can influence condition of Indonesia’s rice market and that the increase in Government Purchase Price (HPP), agricultural credit, and fertilizer subsidy can improve the welfare of the producers and consumers.